2019
DOI: 10.1038/s41598-019-39592-6
|View full text |Cite|
|
Sign up to set email alerts
|

Streptomyces monashensis sp. nov., a novel mangrove soil actinobacterium from East Malaysia with antioxidative potential

Abstract: A new Streptomyces species discovered from Sarawak mangrove soil is described, with the proposed name – Streptomyces monashensis sp. nov. (strain MUSC 1J T ). Taxonomy status of MUSC 1J T was determined via polyphasic approach. Phylogenetic and chemotaxonomic properties of strain MUSC 1J T were in accordance with those known for genus Streptomyces . Based on phylogenetic ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
64
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 61 publications
(66 citation statements)
references
References 101 publications
(126 reference statements)
1
64
0
1
Order By: Relevance
“…It has been suggested that understudied ecosystem hold Streptomyces species which can meet the growing demand of drug discovery and development industry [77] . Researchers who made an effort to study Streptomyces from less explored ecosystems such as mangrove forest were able to discover novel Streptomyces species and Streptomyces strains showing potent antioxidant activities [40,42,66,68,78,79] . dards for potential match.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been suggested that understudied ecosystem hold Streptomyces species which can meet the growing demand of drug discovery and development industry [77] . Researchers who made an effort to study Streptomyces from less explored ecosystems such as mangrove forest were able to discover novel Streptomyces species and Streptomyces strains showing potent antioxidant activities [40,42,66,68,78,79] . dards for potential match.…”
Section: Discussionmentioning
confidence: 99%
“…dards for potential match. Nowadays, GC-MS coupled with NIST mass spectral library is extensively used for determining the bioactive constituents in microbial extracts [42,68,79] . In this experiment, 11 compounds were detected in the methanolic extract MUSC 11: Interestingly 11 compounds were detected by GC-MS in the microbial crude extract MUSC 11 with wide ranging biological activities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In silico prediction and characterization of a microbial secondary metabolite of biosynthetic gene clusters has successfully contributed to the development of new medicines (Loureiro et al 2018). The majority of these metabolites belong to a wide variety of chemical classes and have shown antibiotic and antitumor activities (Law et al 2019). Recently, the cost of genome sequencing has dramatically decreased and allows for the discovery of thousands of gene clusters encoding the biosynthetic machinery for these compounds (Palazzotto and Weber 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Owing to their ability in synthesizing bioactive compounds of various structures, members of Streptomyces have always been in the limelight for the search of pharmaceutically important compounds [1][2][3][4][5][6] . Coupled with their ability to synthesize various bioactive compounds, their unique life cycle and spore formation has allowed these filamentous bacteria to survive and colonize various habitats, covering both terrestrial and marine region [7][8][9][10][11][12][13][14][15][16][17][18] . Streptomyces humi MUSC 119 T was recovered from mangrove soil in east coast of Peninsular Malaysia [19] .…”
Section: Short Introductionmentioning
confidence: 99%